Exploring Host–Commensal Interactions in the Respiratory Tract - Shekhar, Sudhanshu; Schenck, Karl; Petersen, Fernanda Cristina (Frontiers in Immunology, 2018)
Commensal microbes are currently in the limelight in biomedical research because they play an important role in health and disease. Humans harbor an enormous diversity of commensals in various parts of the body, including the gastrointestinal and respiratory tracts. Advancement in metagenomic and other omic approaches, and development of suitable animal models have provided an unprecedented appreciation into the diversity of commensals, and the intricacies of their intimate communication with the host immune system. Most studies have focused on the host-commensal interaction in the gut, while less is known on this relationship in other sites of the body, such as the respiratory tract. In this article, we review emerging data from human and animal studies on the host responses to respiratory commensals, immune cross-reactivity between commensals and pathogens, and use of commensals as a vaccine delivery system. A better understanding of the delicate interplay between commensals and host may aid in efforts to develop effective vaccines and therapeutics.